Synchrotron Radiation Circular Dichroism (SRCD) spectroscopy: New beamlines and new applications in biology. Issue 5 (2007) - Miles Miles, Andrew J. Andrew J.; Hoffmann Hoffmann, Søren Vrønning Søren Vrønning; Tao Tao, Ye Ye; Janes Janes, Robert W. Robert W.; Wallace Wallace, B. A. B. A.
Abstract : New advances in instrumentation, demonstration of proof-of-principle studies, and development of new tools and methods for data analysis and interpretation have enabled the technique of Synchrotron Radiation Circular Dichroism (SRCD) spectroscopy to become a useful tool for structural and functional biology. This paper discusses the characterisation of two new SRCD beamlines, CD1 at the Institute for Storage Rings (ISA), Denmark and 4B8 at the Beijing Synchrotron Radiation Facility (BSRF), China, and new applications of the method for examining biological systems.